Investigation of Scraper Trap System by using Finite Element Method (FEM) (International Journal of Current Engineering and Technology, 2015)
The purpose of this paper is to further the knowledge of pigging and scraper trap in terms ofFEM as a powerful tool.Where reaction forces and expected displacements have been investigated, consequently a new particular design has been suggested for a pig in scraper trap system, thereafter some concluded points have been illustrated clearly
Keywords: Scraper Trap System; FEM etc.